Higher Education and Financial Behavior: The effect of studying mathematics and economics on financial outcomes - Kristoffer B. Hvidberg (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
This paper presents new evidence on the effect of education on financial behavior. In particular, I investigate whether obtaining a degree from a study program with a mathematical or economic curriculum affects individuals future loan default probability. I identify the causal effects of different types of education on financial behavior by exploiting the GPA admission thresholds to higher education programs in a fuzzy regression discontinuity design. I compare people who have applied for the same fields of study but who are quasi-randomly allocated to different different fields of study due to small differences in their GPA from upper secondary school. I estimate the effects using a unique combination of administrative data on admissions to post-secondary education and third party reported data on the universe of personal loans. I find that completing a mathematical or economic field of study decreases the probability of default post graduation for the applicants who did not have one of these fields as their most preferred field of study.
Keywords: G5; I2; 330; Financial Behavior; Education; Regression Discontinuity